Estimation of stroke severity with National Institutes of Health Stroke Scale grading and retinal features: A cross-sectional study. Issue 31 (6th August 2021) - Zhuo, Yuanyuan; Qu, Yimin; Wu, Jiaman; Huang, Xingxian; Yuan, Weiqu; Lee, Jack; Yang, Zhuoxin; Zee, Benny
Abstract : Abstract: To estimate National Institutes of Health Stroke Scale (NIHSS) grading of stroke patients with retinal characteristics. A cross-sectional study was conducted in Shenzhen Traditional Chinese Medicine Hospital. Baseline information and retinal photos were collected within 2 weeks of admission. An NIHSS score was measured for each patient by trained doctors. Patients were classified into 0 to 4 score group and 5 to 42 score group for analysis. Three multivariate logistic models, with traditional clinical characteristics alone, with retinal characteristics alone, and with both, were built. For clinical characteristics, hypertension duration is statistically significantly associated with higher NIHSS score ( P = .014). Elevated total homocysteine levels had an OR of 0.456 ( P = .029). For retinal characteristics, the fractal dimension of the arteriolar network had an OR of 0.245 ( P < .001) for the left eyes, and an OR of 0.417 ( P = .009) for right eyes. The bifurcation coefficient of the arteriole of the left eyes had an OR of 2.931 (95% CI 1.573–5.46, P = .001), the nipping of the right eyes had an OR of 0.092 ( P = .003) showed statistical significance in the model. The area under receiver-operating characteristic curve increased from 0.673, based on the model with clinical characteristics alone, to 0.896 for the model with retinal characteristics alone and increased to 0.931 for the model with both clinical and retinal characteristics combined. Retinal characteristics provided more information than clinical characteristics in estimating NIHSS grading and can provide us with an objective method for stroke severity estimation.